The Chernobyl accident: Can lichens be used to characterize a radiocesium contaminated range? - Gaare, Eldar (Rangifer, 1987)
Many of the lichen species that are important in the lichen dominated plant communities in the Norwegian mountains are important reindeer winter forage. They are also organisms that collect fall-out from the atmosphere. The Chernobyl accident brought, among other, radioactive Cesium, and from lichens this follow the food chain to reindeer and finally man. From region to region this fall-out was unevenly distributed and methods are needed to compare winter ranges and to monitor the developement of radioactive levels in the lichen carpet. Cornicularia divergens, Alectoria ochroleuca, Cetraria nivalis, Cladina mitis, C. stellaris and Stereocaulon pa¬schale was collected in the Dovre mountains to compare species levels and to study collection methods. We found that from spot to spot there is a very large variation between samples, even within the same species. Because of this we are not able to show significant species differences. We found, however, that species from more or less snow free ridgetops, Cornicularia divergens, Alectoria ochroleuca, Cetraria nivalis and Cladina mitis showed less variation and thus must be recommended as the best species for monitoring and comparison of ranges.Tsjernobyl-ulykken: Kan lav nyttes til karakterisering av et radioaktivt forurenset reinbeite?Abstract in Norwegian / Sammendrag: Mange av de lavarter som er viktige i lavdominerte plantesamfunn i de norske fjell er viktige som vinterfor for rein. Disse organismer samler også nedfall fra atmosfæren. Ulykken i Tsjernobyl brakte, blant annet, radioaktivt cesium, og fra lav følger dette næringskjeden til rein og endelig mennesket. Fra område til område var dette nedfallet ujevnt fordelt, og det kreves metoder for å sammenligne vinterområder og for å overvåke utviklingen av det radioaktive nivå i lavmattene. Cornicularia divergens, Alectoria ochroleuca, Cetraria nivalis, Cladina mitis, C. stellaris og Stereocaulon paschale ble samlet på Dovrefjell for å sammenligne artsnivåene og for å studere innsamlings-prosedyrer. Vi fant at det fra sted til sted var en svært stor variasjon, til og med innen samme art. På grunn av dette var vi ikke i stand til å vise statistisk sikre forskjeller mellom artene. Men vi fant at arter fra mer eller mindre snøfrie rabbetopper, Cornicularia divergens, Alectoria ochroleuca, Cetraria nivalis og Cladina mitis viste mindre variasjon og derfor må anbefales som de beste arter for overvåkning og sammenligning av områder.